(untitled) (International Journal of Built Environment and Sustainability, 2024)
This study was conducted to identify categories of urban tree protection legislative provisions (TPLP) implementable by the local planning authorities (LPAs) in Peninsular Malaysia through a deductive thematic analysis of Act 172, Act 267, Act 171, Act 133, Act 536 and Park By-Laws. The results show that Malaysian urban TPLP categories are mainly found only in Act 172 and Act 267, and they are: 1) Tree Felling Prohibition, 2) Tree Preservation Order (TPO), and 3) Tree Protection Planning Conditions. The first category is for the LPAs to prohibit tree felling or other tree damaging activities without their consent. The second category is about orders made by LPAs to protect specific trees or groups of trees in the interests of amenity. The third category is pertaining to conditions imposed by LPAs on a grant of planning permission (Kebenaran Merancang) that requires the applicants to retain and protect any tree in the development. The outcomes of the analysis further suggested that Malaysian protected urban trees can also be group into two: 1) Regulated Trees, and 2) Registered Trees. The former category are trees with girth exceeding 0.8 m (Act 172) and 1.0 m (Act 267) protected by Tree Felling Prohibition provisions. The latter are trees protected by TPO provisions of both Act 172 and Act 267. All protected urban trees are subjects of the Tree Protection Planning Conditions. If properly implemented, the TPLP would be a vital tool for environmental conservation efforts.